Population Pharmacokinetics of Artemether, Lumefantrine, and Their Respective Metabolites in Papua New Guinean Children with Uncomplicated Malaria - Salman, S.; Page-Sharp, Madhu; Griffin, S.; Kose, K.; Siba, P.; Ilett, K.; Mueller, I.; Davis, T. (American Society for Microbiology, 2011)
There are sparse published data relating to the pharmacokinetic properties of artemether, lumefantrine, and their active metabolites in children, especially desbutyl-lumefantrine. We studied 13 Papua New Guinean children aged 5 to 10 years with uncomplicated malaria who received the six recommended doses of artemether (1.7 mg/kg of body weight) plus lumefantrine (10 mg/kg), given with fat over 3 days. Intensive blood sampling was carried out over 42 days. Plasma artemether, dihydroartemisinin, lumefantrine, and desbutyl-lumefantrine were assayed using liquid chromatography-mass spectrometry or high-performance liquid chromatography. Multicompartmental pharmacokinetic models for a drug plus its metabolite were developed using a population approach that included plasma artemether and dihydroartemisinin concentrations below the limit of quantitation. Although artemether bioavailability was variable and its clearance increased by 67.8% with each dose, the median areas under the plasma concentration-time curve from 0 h to infinity (AUC0-∞s) for artemether and dihydroartemisinin (3,063 and 2,839 μg·h/liter, respectively) were similar to those reported previously in adults with malaria.For lumefantrine, the median AUC0–∞ (459,980 μg·h/liter) was also similar to that in adults with malaria. These data support the higher dose recommended for children weighing 15 to 35 kg (35% higher than that for a 50-kg adult) but question the recommendation for a lower dose in children weighing 12.5 to 15 kg. The median desbutyl-lumefantrine/lumefantrine ratio in the children in our study was 1.13%, within the range reported for adults and higher at later time points because of the longer desbutyl-lumefantrine terminal elimination half-life. A combined desbutyl-lumefantrine and lumefantrine AUC0–∞ weighted on in vitro antimalarial activity was inversely associated with recurrent parasitemia, suggesting that both the parent drug and the metabolite contribute to the treatment outcome of artemether-lumefantrine.